2017
DOI: 10.1161/strokeaha.116.016149
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors of the Aspiration Component Success of a Direct Aspiration First Pass Technique (ADAPT) for the Endovascular Treatment of Stroke Reperfusion Strategy in Anterior Circulation Acute Stroke

Abstract: Results-Among the 347 patients (occlusion sites: middle cerebral artery=200, 58%; internal carotid artery Siphon=89, 25%; Tandem=58, 17%), aspiration component led to successful reperfusion (modified thrombolysis in cerebral infarction 2b/3 scores) in 55.6% (193/347 patients), stent retrievers were required in 40%, and a total successful final reperfusion rate of 83% (288/347) was achieved. Overall, procedural complications occurred in 13.3% of patients (48/347). Modified Rankin Scale score of 0 to 2 at 90 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 34 publications
8
36
1
Order By: Relevance
“…Likely explanations for this discrepancy could be the ‘real world’ design of our series as well as the frequencies’ discrepancy of ICA occlusions treated in our study (with ~30%) as opposed to the frequency in the ASTER trial (with ~10%). Clot length and overall mass is bigger in ICA occlusions leading to more device passes and lower reperfusion rates 24. The results of our stent-retriever group correlate well with the angiographic results published in the MR-CLEAN and THRACE trials 15 25.…”
Section: Discussionsupporting
confidence: 83%
“…Likely explanations for this discrepancy could be the ‘real world’ design of our series as well as the frequencies’ discrepancy of ICA occlusions treated in our study (with ~30%) as opposed to the frequency in the ASTER trial (with ~10%). Clot length and overall mass is bigger in ICA occlusions leading to more device passes and lower reperfusion rates 24. The results of our stent-retriever group correlate well with the angiographic results published in the MR-CLEAN and THRACE trials 15 25.…”
Section: Discussionsupporting
confidence: 83%
“…Blanc et al 24 identified clot location as the main factor related to DTA efficacy with a high rate of successful recanalization for M1 occlusions and a low rate for carotid artery terminus occlusions. The authors suggested that there was a more effective interaction in the M1 location between the aspiration catheter and the clot due to the better correspondence between the vessel and the catheter diameters.…”
Section: Discussionmentioning
confidence: 99%
“…The ADAPT approach may present with a lower risk of embolic complications due to the aspiration component allowing an en bloc clot extraction in up to 78%12 without passage through the thrombus, theoretically reducing the risk of fragmentation. Nevertheless, our results support the fact that SR alone without aspiration is an independent factor for ACAE, with a 2.6-fold increased risk.…”
Section: Discussionmentioning
confidence: 99%